MATWIN: bridging the gap between academic research and industry - Reiffers, Josy (Hum Genomics, 2015)
MATWIN (Maturation and Accelerating Translation With INdustry) is part of the nationwide effort to support cancer innovation. This unique program is willing to support innovative research projects providing tools, resources, and staff dedicated to project leaders wishing to optimize the industrial attractiveness of their project. The overall objective is clear: fight cancer always more effectively.